Designing a Tool for Assisting in the Setup of Optical Motion Capture Systems - BATIS, EMMANUEL; BYLUND, MATHIAS (My University, 2017)
As optical motion capture systems grow bigger and more complex, the need for mobility when interacting with these systems becomes apparent due to the increasing spatial distances between system components. Seeing how these technologies rapidly evolve and how their usage is becoming more common, providing a way of assisting setup technicians is clearly valuable. This thesis documents the design- and creation process of a tool that provides the aforementioned assistance. The tool enables its users to visualize the real-time output of every camera in a system. At the same time it provides a way of making adjustments on-the-fly without the need for excessive maneuvering, effectively reducing the amount of personnel needed for setting up the system. Moreover, this tool acts as a technological statement which proves that it is possible to create cross-platform mobile tools that interact with an optical motion capture system in real-time and by that removes the need to maintain several applications for different platforms.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science